Hubungan Peregangan Dengan Nyeri Sendi Di Usia Lanjut - Sri Handayani; Sujono Riyadi (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: Stretching or stretching is an important link between a static life and an active life that keeps muscles flexible. Stretching in the elderly is carried out to increase muscle elasticity, because the elderly are always associated with changes in muscle elasticity (Suwardana, 2012). Purpose: To determine the relationship of stretching to joint pain in the elderly through several sources of research conducted previously. Methods: This research is in the form of literature review or literature research. The nature of this research is descriptive analysis, namely the regular decomposition of the data that has been obtained. The data used in this study is secondary data, namely data obtained from ten research journals which are sampled and analyzed. Search for journals through Google Schoolar, and Pubmed. Results: From all journals that have been analyzed, the average journal shows a very significant Hypothesis value p = 0.000 (p <0.05). Therefore, it can be concluded that Ho is rejected and Ha is accepted, so that there is a significant difference in the mean score of the pain scale between before and after being given stretching exercises. So clearly there is a significant relationship between stretching and joint pain. Conclusion: Based on the results of research from all the journals that have been analyzed, it is found that there is a relationship between stretching and the reduction of joint pain in the elderly who experience pain. On average, the elderly experienced moderate pain (4-6) before being given stretching exercises, and after being given stretching exercises, they experienced a decrease in mild pain (1-3). So it can be concluded that Ho is rejected and Ha is accepted, so that there is a significant difference in the mean score of the pain scale between before and after being given stretching exercises.